Total Absolute Difference Edge Irregularity Strength of Several Ladder-type Graphs - Faisal Susanto; Kristiana Wijaya (Universitas Negeri Gorontalo, 2026)
This paper studies edge irregular total absolute difference labeling for several classes of ladder-related graphs, namely triangular ladders, alternating triangulated ladders, and double triangulated ladders. By deriving coinciding lower and upper bounds, the precise values for the total absolute difference edge irregularity strength of these graphs are successfully established.